2009
DOI: 10.1017/s002238160909094x
|View full text |Cite
|
Sign up to set email alerts
|

Partisanship, Voting, and the Dopamine D2 Receptor Gene

Abstract: Previous studies have found that both political orientations (Alford, Funk, and Hibbing 2005) and voting behavior (Fowler, Baker, and Dawes 2008; are significantly heritable. In this article we study genetic variation in another important political behavior: partisan attachment. Using the National Longitudinal Study of Adolescent Health, we show that individuals with the A2 allele of the D2 dopamine receptor gene are significantly more likely to identify as a partisan than those with the A1 allele. Further, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 71 publications
2
60
0
Order By: Relevance
“…15 More broadly, the notion of environment-specific effects suggests that the link between personality and attitudes is likely to be a function of features of political environments such as social networks that are of growing interest across the social sciences (see, e.g., Christakis and Fowler 2009;Heaney and McClurg 2009). Likewise, the role of individual-level genetic differences in explaining political opinions and behavior is an area of ongoing work (e.g., Alford, Funk, and Hibbing 2005;Dawes and Fowler 2009;Eaves and Hatemi 2008;Fowler, Baker, and Dawes 2008;Hatemi et al 2009;Hatemi et al 2007;Martin et al 1986;Settle, Dawes, and Fowler 2009). Although there may be more direct links between genetics and political outcomes, the notion that contexts provide meaning to political stimuli seems like a promising theoretical conduit for how individual-level genetic differences, which are correlated with dispositional traits, affect political attitudes and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…15 More broadly, the notion of environment-specific effects suggests that the link between personality and attitudes is likely to be a function of features of political environments such as social networks that are of growing interest across the social sciences (see, e.g., Christakis and Fowler 2009;Heaney and McClurg 2009). Likewise, the role of individual-level genetic differences in explaining political opinions and behavior is an area of ongoing work (e.g., Alford, Funk, and Hibbing 2005;Dawes and Fowler 2009;Eaves and Hatemi 2008;Fowler, Baker, and Dawes 2008;Hatemi et al 2009;Hatemi et al 2007;Martin et al 1986;Settle, Dawes, and Fowler 2009). Although there may be more direct links between genetics and political outcomes, the notion that contexts provide meaning to political stimuli seems like a promising theoretical conduit for how individual-level genetic differences, which are correlated with dispositional traits, affect political attitudes and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have already begun discovering specific genes associated with political behavior, which may be the first few pieces in the puzzle to understanding the biology that underlies it. For example, two studies Dawes and Fowler 2008) recently identified variants of three genes that are positively correlated with voter turnout. The genes they studied are known to influence social behavior via the dopaminergic and serotonergic systems, suggesting that voting may, in fact, be a prosocial act.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, scholars have found that political attitudes related to vote choice are also heritable (Hatemi et al 2007) as is the strength of partisan attachment (Hatemi et al 2009a;Settle, Dawes, and Fowler 2009). Likewise, genetic variation is important for explaining variation in political behaviors that are known to be influenced by ideology, like voting and other forms of political participation (Fowler, Baker, and Dawes 2008;Dawes and Fowler 2009). These findings suggest that we should revise our environment-only understanding of political attitudes and ideology.…”
mentioning
confidence: 99%